2019
DOI: 10.24251/hicss.2019.620
|View full text |Cite
|
Sign up to set email alerts
|

Maturity Models in the Age of Industry 4.0 – Do the Available Models Correspond to the Needs of Business Practice?

Abstract: Maturity models (MMs) enable users to identify the need for change and to derive the necessary measures to accompany the change process. Existing literature reviews indicate that the number of available models has increased sharply in recent years. At the same time, it is found that the number of model applications does not keep up with the pace of development. Against the background of the current digitization trend, this article empirically investigates which models are actually used in business practice. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 29 publications
1
37
0
3
Order By: Relevance
“…A recent study revealed that almost all scientific and many consultancy MMs (in the field of Industrial Internet) are still not being used or are even unknown in business practice, although potential applicants stated a need for and interest in these models in general [21]. As this discrepancy comes as a surprise, we assume a weak point either in the development or application of MMs (Fig.…”
Section: A Meta Model For Staged Maturity Modelsmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study revealed that almost all scientific and many consultancy MMs (in the field of Industrial Internet) are still not being used or are even unknown in business practice, although potential applicants stated a need for and interest in these models in general [21]. As this discrepancy comes as a surprise, we assume a weak point either in the development or application of MMs (Fig.…”
Section: A Meta Model For Staged Maturity Modelsmentioning
confidence: 95%
“…In other words, syntax and semantics vary across MMs, which is why, on the one hand, companies (as applicants) do not use or apply the models, as they simply do not understand their structure and effects. On the other hand, researchers tend to develop even more and new MMs, as they do not recognize existing models as similar or comparable MM approaches (i.e., from 2016 to 2018, 18 new MMs had been developed in the domain of Industry 4.0 [21]). What is needed is an overarching, holistic conceptual framework that can unify and standardize the individual objectives and goals.…”
Section: A Meta Model For Staged Maturity Modelsmentioning
confidence: 99%
“…Industry 4.0 readiness models are important for the organizations as it will help in understanding the present position of the organization and the change that is required for the application of Industry 4.0. In the Industry 4.0 implementation sense, it can be seen as a management tool, which will help in realignment, reconfiguration and renewal of organizations capabilities and capacities [25].Furthermore, the application of Industry 4.0 will result ina creation of new business models, strategies, KPI, etc [4,6]. Thus, it is pertinent to…”
Section: Industry 40mentioning
confidence: 99%
“…Apparently, the creators of the different models have not yet succeeded in translating their abstract concepts into practicable tools. The authors try to understand the purpose behind using maturity models in practice, to identify concrete practical requirements and to deliver recommendations for future research and development of the existing maturity models [1].…”
Section: Contributionsmentioning
confidence: 99%